Mistletoes could moderate drought impacts on birds, but are themselves susceptible to drought-induced dieback. Issue 1978 (13th July 2022) - Crates, Ross; Watson, David M.; Albery, Gregory F.; Bonnet, Timothée; Murphy, Liam; Rayner, Laura; Stojanovic, Dejan; Timewell, Chris; Meney, Beau; Roderick, Mick; Ingwersen, Dean; Heinsohn, Robert
Abstract : Mistletoes are hemiparasitic plants and keystone species in many ecosystems globally. Given predicted increases in drought frequency and intensity, mistletoes may be crucial for moderating drought impacts on community structure. Dependent on host vascular flows, mistletoes can succumb to stress when water availability falls, making them susceptible to mortality during drought. We counted mistletoe across greater than 350 000 km 2 of southeastern Australia and conducted standardized bird surveys between 2016 and 2021, spanning a major drought event in 2018–2019. We aimed to identify predictors of mistletoe abundance and mortality and determine whether mistletoes might moderate drought impacts on woodland birds. Live mistletoe abundance varied with tree species composition, land use and presence of mistletoebirds. Mistletoe mortality was widespread, consistent with high 2018/2019 summer temperatures, low 2019/2020 summer rainfall and the interaction between summer temperatures and rainfall in 2019/2020. The positive association between surviving mistletoes and woodland birds was greatest in the peak drought breeding seasons of 2018/2019 and 2019/2020, particularly for small residents and insectivores. Paradoxically, mistletoes could moderate drought impacts on birds, but are themselves vulnerable to drought-induced mortality. An improved understanding of the drivers and dynamics of mistletoe mortality is needed to address potential cascading trophic impacts associated with mistletoe die-off.